Peranan Audit Internal dalam Menunjang Efektivitas Pemberian Kredit - Rini Susiani; Rosa Fitriana; Syafdinal (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to find out the role of Internal Audit (independence and objectivity, professional skill and accuracy, and integrity) in supporting the effectiveness of providing credit, case study at the Bank X Bandung branch offices. The population in this study was 30 people, with a sampling technique using non-probability sampling with a saturated sampling technique. The analytical method used in this research is multiple linear regression analysis at a significance level of 5%. The program for analyzing data uses the Statistical Package for Social Sciences (SPSS) Ver 25.0. The research results show that Independence and Objectivity, Professional Skills and Accuracy, and Integrity have a role in supporting the effectiveness of providing credit at the Bank X Bandung Branch Office.